2016
DOI: 10.1111/jcpt.12486
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between multicriteria decision analysis-based ranking and intuitive ranking for pharmaceutical benefit-risk profiles in a hypothetical setting

Abstract: Observed discrepancies between the rankings seemed to be primarily attributed to the structural characteristics of MCDA, which assumes that evaluation on each benefit and risk component should have monotonic impact on final scores. It would be difficult for MCDA to reflect commonly observed non-monotonic preferences for risk and benefit profiles. Possible drawbacks of MCDA should be further investigated prior to the real-world application of its benefit-risk assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The selection stage resulted in 18 articles in English (HOSHIKAWA et al, 2017;MARSH et al, 2017;SCHEY et al, 2017;AL-BRADRIYEH et al, 2016;GREEF-VAN DER SANDT et al, 2016;GOETGHEBEUR et al, 2016;KOLASA et al, 2016;NWOKORO et al, 2016;BROEKHUIZEN et al, 2015;HSU et al, 2015a;HSU et al, 2015b;RAMLI et al, 2013;ERJAEE et al, 2012;GOETGHEBEUR et al, 2012;CHEN et al, 2011;TERVONEN et al, 2011;FANG et al, 2010;PEREZ ENCINAS et al, 1998). The studies referred to several diseases according to specific evaluation criteria, as shown in the table below.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The selection stage resulted in 18 articles in English (HOSHIKAWA et al, 2017;MARSH et al, 2017;SCHEY et al, 2017;AL-BRADRIYEH et al, 2016;GREEF-VAN DER SANDT et al, 2016;GOETGHEBEUR et al, 2016;KOLASA et al, 2016;NWOKORO et al, 2016;BROEKHUIZEN et al, 2015;HSU et al, 2015a;HSU et al, 2015b;RAMLI et al, 2013;ERJAEE et al, 2012;GOETGHEBEUR et al, 2012;CHEN et al, 2011;TERVONEN et al, 2011;FANG et al, 2010;PEREZ ENCINAS et al, 1998). The studies referred to several diseases according to specific evaluation criteria, as shown in the table below.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the alternatives evaluated, 11 studies reported the drugs analyzed, while four cited only their therapeutic classes (HOSHIKAWA et al, 2017;BROEKHUIZEN et al, 2015;FANG et al, 2010). In three studies, the therapeutic class was not reported [two referring to orphan drugs (SCHEY et al, 2017;KOLASA et al, 2016) Different techniques of multicriteria analysis were applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 46 model application studies evaluated pharmaceuticals (24 studies), medical devices (12), health interventions (9) and general health technologies (1). Pharmaceuticals constituted the subject matter of investigations in the following disease areas: rare diseases (none of which contained orphan cancer indications) [5660], cancer [6163], depression [64, 65], cerebrovascular diseases [66, 67], pain-relief [68, 69], age-related macular degeneration [70], overactive bladder [71], idiopathic short stature [72], Turner syndrome [73], psoriasis [74], hypercholesterolemia [75], chronic obstructive pulmonary disease (COPD) [76] and relapsing–remitting multiple sclerosis (RRMS) [77]. Two studies developed models to compare pharmaceuticals targeting several diseases [27, 78].…”
Section: Resultsmentioning
confidence: 99%
“…There are limits to involve a large number of participants in a face-to-face setting. MCDA studies have been involving much smaller numbers of participants than large patient preference studies[19, 21, 24, 26, 27, 31, 33, 36, 57, 59, 60, 62, 63, 65, 66, 72, 73, 75, 78, 80, 82, 84, 9799, 101103, 106, 109, 111, 113, 116, 121, 123, 126, 129, 131, 132, 139, 142, 144, 147, 148, 153, 162]#3Participant Difficulties in Evaluation Processes (SOCIAL) (33 studies)Participants face difficulties in interpreting data or in understanding evaluation processes; they also face cognitive difficulties in providing judgments (for instance using swing weighting, comparing mild and serious events, understanding orders of magnitude, interpreting weighting coefficients). Evaluation judgments may be frame-dependent (e.g.…”
Section: Resultsmentioning
confidence: 99%